169 Robotic radical hysterectomy (RRH) versus chemo-radiation (CRT) followed by type 1 robotic hysterectomy for 1B2 cervical cancer (CC). (18th September 2019) - Fitzsimmons, C; Stephens, A; Kennard, J; Manyam, M; Pepe, J; DeCoff, K; Ahmad, S; McKenzie, N; Kendrick, J; Holloway, R
Abstract : Objectives: To compare peri-operative outcomes, RFS, and OS for patients with FIGO-2014 stage 1B2 CC treated by RRH versus CRT and brachytherapy (BT) followed by Type 1 robotic hysterectomy (RH). Methods: Patients with FIGO-2014 stage 1B2 CC (1/2007–12/2017) who underwent RRH (Group A) or CRT and VB followed by RH (Group B) were identified. Inclusion criteria included: adenocarcinoma or squamous cell histology; >12 month follow-up, tumor size (TS) >4 cm by either pathology in A or radiographic/clinical criteria in B, and no evidence of para-aortic node metastasis on imaging. Results: 15 group A (median TS=5.0±1.2 cm) and 31 group B (median TS=5.0±1.0 cm) pts were identified. Pre-operative imaging reported no positive nodes in A compared to 8 (25%) in B. 12(80%) required adjuvant CRT in group A. Median follow-up time was 64±34.6 months for A versus 33±32.7 months for B ( p =0.059). No (+) para-aortic nodes were identified in A versus 5 cases in B ( p =0.15). Recurrences were diagnosed in 3 (20%) A and 7 (22.5%) B cases. Median time to recurrence was 15.0±49 months for A compared to 11.0±7 months in B. 5-year RFS and OS was 80% & 84.7% (A) versus 78% & 83.9% (B). Complications included urinary fistula (n=3; 20%) and cuff dehiscence (n=1; 6.7%) in A versus one each for B (3.3%). Conclusions: Despite having higher risk factors including para-aortic metastasis, patients with IB2 CC treated with CRT/BT/RH had similar RFS/OS to RRH, and with less fistulae and cuff dehiscence.